Development and Implementation of the PD-CARE Model for Student Support in the Digital Era - สุริโย, ปัทมาพร; Boonsong, Kanchana (Journal of MCU Phetchaburi Review, 2026)
This research aimed to (1) develop a student support system model using digital technology at Pa Deng Wittaya School under the Secondary Educational Service Area Office Phetchaburi and (2) examine the results of implementing the developed model. The study employed a Research and Development (R&D) approach conducted in two phases. The first phase investigated the current conditions and needs of the student support system through interviews with school administrators and teachers, together with a review of related documents and research in order to synthesize and develop a digital-based student support model. The second phase involved the implementation of the developed model at Pa Deng Wittaya School. The research instruments included semi-structured interview forms, a model feasibility evaluation form, and operational record forms. Data were analyzed using content analysis and qualitative data synthesis. The findings revealed that the developed student support system model in the digital era is the PD-CARE Model, consisting of six key processes: Plan, Do, Collect, Action, Reflection, and Evaluation. The model integrates the management of the student support system with digital technology for systematic student data collection and utilization. The implementation results indicated that the school was able to manage the student support system more systematically. Teachers could collect individual student data, classify students according to their needs, and use the information for student promotion, prevention, and problem-solving appropriately, leading to more comprehensive and effective student support.